Activity based costing method dalam penentuan harga pokok produksi pada Industri Batik di Kota Jambi - Kusumastuti, Ratih; Muhammad Ridwan; Dios Nugraha Putra (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the accuracy of the calculation of the cost of production of batik in the batik industry in Jambi City using the Activity Based Costing Method and to determine the difference in product costs using the Activity Based Costing Method and the system applied by the batik industry in Jambi City. The research object to be studied is the application of the Activity Based Costing Method in the batik industry in Jambi City. The population of this research is the batik industry in Jambi City. Samples were selected based on predetermined criteria. This study uses qualitative and quantitative descriptive analysis methods, namely qualitative descriptive analysis, namely explaining, summarizing various conditions and problems that arise in the object of the study. Based on what happened and compared with the actual situation on the object under study. The results showed that the Production Cost with the ABC system approach resulted in lower costs. This cost is obtained by calculating the labor cost rate and factory overhead costs. Where direct labor costs are the most significant costs in production activities. The cost calculation makes a significant difference. The cost calculation carried out by the company produces a greater cost, and has a difference for each unit of product. This is because the overhead rates have not been allocated properly. So it is necessary to calculate with a more accurate approach, namely with an alternative approach to the Activity Based Costing method so that it can produce accurate costs.